REGARDING DETERMINATION OF MILLET GRAIN ENZYME (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Tariq is one of the most common grain crops in Uzbekistan. Cereal made from its grain is famous for its taste and richness. Bread made from millet is small in size and hardens quickly. Millet waste (from processing) is a good feed for cattle. This article describes in detail the biological properties of millet grain as well as the determination of its enzyme.